Education System in the Era of Smart Society 5.0 - Indra, Arjuna (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research discusses the Education System in the Smart Society 5.0 Era. The aim of this research is to describe the Education System in the Smart Society 5.0 Era. The research method used is qualitative research using a library approach, a library approach, namely studies that use data analysis based on written material. Library materials include published notes, books, magazines, newspapers, manuscripts, journals or articles. From the research results, it is clear that education as a system is a complete unit in education which consists of components that are interconnected with each other in order to achieve the desired goals. These components are the basis of education, educational objectives, educational content, educational methods, tools, educated, educators and objectives.